2016
DOI: 10.1128/jvi.01636-16
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two PMLs: Elements Regulating a Differential Substrate Recognition by the ICP0 E3 Ubiquitin Ligase of Herpes Simplex Virus 1

Abstract: Infected cell protein 0 (ICP0) of herpes simplex virus 1 (HSV-1) is an ␣ gene product required for viral replication at low multiplicities of infection. Upon entry, nuclear domain 10 (ND10) converges at the incoming DNA and represses viral gene expression. ICP0 contains a RING-type E3 ubiquitin ligase that degrades the ND10 organizer PML and disperses ND10 to alleviate the repression. In the present study, we focused on understanding the regulation of ICP0 E3 ligase activity in the degradation of different ICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…For this purpose, we infected U2OS cells with RHG103, in which ICP0 lacks C-terminal residues 669 to 775, or with RHG108 (18), in which ICP0 lacks residues 669 to 775 and at the same time contains the C116G/C156A substitutions. In previous studies, we showed that ICP0 ΔC maintained its ability to degrade PML but that ICP0 ΔC-RFm did not (18,23). Consistent to what we saw in RHG103-infected HEL cells (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For this purpose, we infected U2OS cells with RHG103, in which ICP0 lacks C-terminal residues 669 to 775, or with RHG108 (18), in which ICP0 lacks residues 669 to 775 and at the same time contains the C116G/C156A substitutions. In previous studies, we showed that ICP0 ΔC maintained its ability to degrade PML but that ICP0 ΔC-RFm did not (18,23). Consistent to what we saw in RHG103-infected HEL cells (Fig.…”
Section: Resultssupporting
confidence: 90%
“…We first took a recombinant virus, RHG120, in which ICP0 contains the C116G/C156A substitutions (ICP0 RFm) (18) and exhibits substantial defects in E3 ligase activity and viral replication during infection of nonpermissive HEL and HEp-2 cells (23). We compared the subcellular distributions of ICP0 RFm late during infection in both HEL and U2OS cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ICP0 utilizes different motifs of PML-NBs fusion and SUMO interaction [ 72 ], suggesting different molecular mechanisms of PML- ICP0 interaction and degradation. More so, among the PML isoforms, different methods of interactions and degradation were observed to be utilized by ICP0 in Hep-2 and U2OS cells [ 73 ]. Hembram and colleagues identified a bona fide SIM in ICP0 which is essential to target SUMOylated PML.…”
Section: Hsv Immune Evasion Mechanismsmentioning
confidence: 99%
“…It is first detected at a dynamic nuclear structure termed nuclear domain 10 (ND10) 7 . The E3 ubiquitin ligase activity of ICP0 triggers the degradation of ND10 organizer proteins, promyelocytic leukemia (PML) protein, and speckled protein 100 kDa (Sp100) 8,9,10 . After the loss of organizer proteins, ND10 nuclear bodies are dispersed and ICP0 is diffused to fill the entire nucleus 4,11 .…”
Section: Introductionmentioning
confidence: 99%